2018
DOI: 10.1186/s40069-018-0290-3
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Glass as Aggregate for Architectural Mortars

Abstract: The possibility of recycling mixed colour waste glass as it is for manufacturing decorative architectural mortars, has been investigated. In mortars, the 0-33-66-100% of calcareous gravel volume has been replaced with recycled glass cullets, with no other inorganic addition. To mitigate the possible alkali-silica reaction, mixes with a hydrophobic admixture were also compared. The obtained results show that the replacement of calcareous gravel with glass cullets of similar grain size distribution permits to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 37 publications
2
5
0
1
Order By: Relevance
“…In this study, for an addition of 20 wt.% glass sand, the modulus of elasticity was about 3% higher than for the base mix. The same phenomenon was observed by Tittarelli et al [ 36 ], but for coarse glass aggregate. This may be due to the fact that the modulus of elasticity for glass is higher than sand [ 59 ].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, for an addition of 20 wt.% glass sand, the modulus of elasticity was about 3% higher than for the base mix. The same phenomenon was observed by Tittarelli et al [ 36 ], but for coarse glass aggregate. This may be due to the fact that the modulus of elasticity for glass is higher than sand [ 59 ].…”
Section: Resultssupporting
confidence: 87%
“…Kou and Poon [ 35 ] achieved a negative effect on bonding and a reduction in strength by using glass as a coarse aggregate in concrete. The same phenomenon was observed by Tittarelli et al [ 36 ]. According to Lee et al [ 37 ], the use of glass aggregates with a particle size of 2.36–5 mm or 5–10 mm in concrete causes alkali-silica reaction (ASR) expansion and the strength reduction.…”
Section: Introductionsupporting
confidence: 88%
“…Yu et al [ 62 ] reported that the glass cullet used as aggregate in concrete enhanced its mechanical properties. Limbachiya et al [ 63 ] and Tittarelli et al [ 64 ], however, obtained the same mechanical performances for concrete mixes with addition of glass sand up to 15%. It was found that the use of glass cullet as replacement for coarse aggregate is not satisfactory owing to the reduction of the bonding between the aggregate and the cement matrix, and a reduction of strength [ 65 ].…”
Section: Introductionmentioning
confidence: 88%
“…The glass used for LCD panels is generally alkali-free; nevertheless, the content of alkali was assessed and had a very low result (Ca 68.9, Na 28.5, K 4.2, and Mg 0.5 mg/kg as reported by Ruello et al [24]). In any case, concerning the risk of an alkali-silica reaction (ASR), it is possible to fully replace traditional calcareous gravel with waste glass as recycled aggregate for the production of mortars, without any particular addition or admixture when glass is finely grinded, as in this case [24,37]. Preliminary washing removes sulphate from the scraps, and they are mixed with water, Portland cement, sand and lime, or calcium carbonate to produce mortars with different qualities [24].…”
Section: Methodsmentioning
confidence: 99%